HetNet Micro dan Pico Cell untuk AMC UE 10 GHz menggunakan SKE pada Lingkungan Bergedung - Andrita Ceriana Eska Andrita; Wahyu Muldayani (Politeknik Aceh, 2023)
User Equipment (UE) was moved at trajectory around buildings. That UE used 10 GHz frequency. Single Knife Edge (SKE) method used for diffraction mechanism. UE trajectory through HetNet (Heterogeneous Networks) consist of microcell and picocell. UE propagation with uplink condition, and AWGN channel. AMC (Adaptive Modulation and Coding) that used MCS (Modulation and Code Scheme) such as QPSK, 16QAM, and 64QAM. Coverage percentages that used with Selection Combining HetNet obtained 95,52%, NodeBase microcell 88,05%, and NodeBase picocell 56,71%. The percentage of selection combining with 64 QAM modulation obtained 70,11%.